Intelligent Fe–Mn Layered Double Hydroxides Nanosheets Anchored with Upconversion Nanoparticles for Oxygen‐Elevated Synergetic Therapy and Bioimaging. Issue 46 (26th October 2020) - Jia, Tao; Wang, Zhao; Sun, Qianqian; Dong, Shuming; Xu, Jiating; Zhang, Fangmei; Feng, Lili; He, Fei; Yang, Dan; Yang, Piaoping; Lin, Jun
Abstract: Multimodal synergistic therapy based on photodynamic therapy (PDT), photothermal therapy (PTT), and chemodynamic therapy (CDT) has attracted increasing attention in cancer therapy. However, the scant therapeutic efficiency is always a barrier for further application. Herein, a smart tumor microenvironment (TME) responsive nanocatalysts are developed by adopting Fe–Mn layered double hydroxides (FeMn‐LDH) as an effective photothermal nanocarrier to load mesoporous silica and chlorin e6 (Ce6)‐covalently coated upconversion nanoparticles (UCSP) for multimodal imaging for directed therapy. Under acidic TME, FeMn‐LDH degrades into Fe 3+ and Mn 2+ ions to initiate a Fenton‐like reaction inducing CDT and enhancing magnetic resonance imaging. Additionally, Fe 3+ can decompose H2 O2 to oxygen (O2 ), enhancing PDT guided by UCSP. As a representative noninvasive imaging probe, the upconversion luminescence will recover after decomposition of FeMn‐LDH, and provide high‐resolution upconversion luminescent imaging guidance for pinpointed PDT. Moreover, the photothermal properties of FeMn‐LDH can further enhance CDT effects. The synergistic therapy and multifunctional imaging can realize the integration of diagnosis and treatment. Abstract : In this article, for the first time an intelligent all‐in‐one nanoplatform is designed by anchoring mesoporous upconversion nanoparticles on Fe–Mn layered double hydroxides nanosheets for synergetic photodynamic therapy, photothermal therapy, and chemodynamic therapy under the acid tumor environment and laser irradiation, which can be monitored via feasible computed tomography imaging and enhanced T 1 / T 2 ‐weighted MR imaging, thus realizing the combination of diagnosis and treatment.